2020
DOI: 10.3390/ijerph17186596
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Life and Marital Status on the Motivations of Ultramarathoners: The Karkonosze Winter Ultramarathon Case Study

Abstract: The aim of this study was to investigate how family life and marital status influence the motivations of ultramarathoners. Two-hundred-sixty-seven Polish athletes participated in the diagnostic survey during the Karkonosze Winter Ultramarathon. The Polish version of the Motivation of Marathoner Scale was used. The motivations of ultra-runners were investigated among the following groups of respondents: people in a relationship/marriage; singles; people with children vs. childless people; people who run alone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…Only partial concordance can also be seen with the study performed by Stempie ń [52], who showed statistically significant differences in motivation behind marathon running between men and women and noted that unrelated to performance were preferred by female runners. The dominance of the weight concern motive among women shown in our study was in turn recognised by Ogles and Masters [53] and Waśkiewicz et al [49], and the emphasis on the sports competition motive among men was confirmed in the study by Malchrowicz-Mośko and Waśkiewicz [54], which was conducted on novice runners in Poland when surveying participants taking part in Parkrun-runs organised in parks or other green areas over a distance of 5 kilometres. Overall, however, these results are only partially consistent with our study, as we did not show that female motivation was also associated with affiliation and self-esteem.…”
Section: Discussionsupporting
confidence: 78%
“…Only partial concordance can also be seen with the study performed by Stempie ń [52], who showed statistically significant differences in motivation behind marathon running between men and women and noted that unrelated to performance were preferred by female runners. The dominance of the weight concern motive among women shown in our study was in turn recognised by Ogles and Masters [53] and Waśkiewicz et al [49], and the emphasis on the sports competition motive among men was confirmed in the study by Malchrowicz-Mośko and Waśkiewicz [54], which was conducted on novice runners in Poland when surveying participants taking part in Parkrun-runs organised in parks or other green areas over a distance of 5 kilometres. Overall, however, these results are only partially consistent with our study, as we did not show that female motivation was also associated with affiliation and self-esteem.…”
Section: Discussionsupporting
confidence: 78%
“…Our results showed that health orientation motives to participate of ultramarathoners were the lowest, followed by marathon runners and 5K runners. For their part, Malchrowicz-Mośko and Waśkiewicz [22] analyzed the impact of family and partner relationships on the motivation behind participating in ultramarathons and found that running ultramarathons can be a threat to the relationship. It is therefore good practice to start running together or organize running events together involving family members.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, motivations related to running a marathon have been addressed in the literature [13][14][15]. Moreover, in an effort to understand which motives are behind a very demanding effort like an ultramarathon, several studies have been carried out in the last decade [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have been dedicated to motivations of ultramarathon runners. Frick (2011) examined motives of male and female ultramarathon runners, Krouse et al (2011) evaluated motives of female ultramarathon participants, Malchrowicz-Mośko and Waśkiewicz (2020) and Thuany et al (2021) analyzed motivation of an ultramarathoner in relation to their family life and marital status or socioeconomic status. They indicated that the most important motivations for running were related to personal goal achievement, health orientation, and selfesteem.…”
Section: Introductionmentioning
confidence: 99%